Exploration of Argumentation and Scientific Reasoning Ability in Phenomenon-Based Argument-Driven Inquiry Learning in Newton's Law Material - Dibyaratna Syarqiy; Lia Yuliati; Ahmad Taufiq (Postgraduate, University of Mataram, 2023)
The ability of argumentation and scientific reasoning is part of scientific literacy which is a requirement for learning science. Students get knowledge according to the understanding of scientists, which is important for students to have, especially in Newton's law material, but learning in the classroom currently has not developed argumentation and scientific reasoning skills properly. This study used a mixed method design with an embedded experimental design carried out offline. This research design was used in order to obtain an in-depth picture of students' argumentation and scientific reasoning abilities. The results showed that students' argumentation and scientific reasoning abilities increased significantly after being given the phenomenon-based Argument-Driven Inquiry (ADI) learning model. This learning has a moderate effect on argumentation skills and a very large one on students' scientific reasoning. Even though students' argumentation abilities have increased significantly, on average students still have difficulty in associating a phenomenon with the appropriate Newton's Laws. Scientific reasoning students also experience positive changes. This is evidenced by the increase in post-test scores and effect sizes which are in the very large category